Bud-Kit as a classroom learning tool / Nur Afrina Jasmin Hassanudin, Muhammad Zikry Yusri and Nur Suraya Abdullah - Hassanudin, Nur Afrina Jasmin; Zikry Yusri, Muhammad; Abdullah, Nur Suraya (Faculty of Plantation and Agrotechnology, 2023)
Some students find it challenging to grasp the concepts taught in class about theoretical plant propagation techniques. The propagated plants failed because they unable to demonstrate the correct propagating technique during completing their assessment. Hence, Bud-Kit was designed to enable the lecturers to bring hands-on-activities into their classrooms. Bud- Kit also developed with aim to provide students with hands-on experience during classroom learning session and this could enhance the students psychomotor and they could apply the skills on real situation. Bud-Kit is equipped with a knife, scissors, and models of plant parts as source of scion and rootstock. The instructions and illustrations of the various budding technique also provided inside the kit. Through the use of Bud-Kit during classroom learning, students have had the chance to understand the theory learned and put it into practice by using the kit provided during the learning session. Prior to executing the real task, this initiative has been able to assist students in understanding the correct technique of in propagating plant species using budding technique. Moreover, it can enhance their knowledge and abilities, allowing them to successfully produce new clone through budding techniques.